PENGARUH METODE BELAJAR E-LEARNING TERHADAP KETERAMPILAN SISWA JURUSAN TEKNIK KENDARAAN RINGAN (TKR) - toumahuwjunus; Ibadja P Tamba; Bastian Rikardo Parhusip (GEARBOX: Jurnal Pendidikan Teknik Mesin, 2022)
ABSTRACT                The purpose of this study is to find out whether there is a significant influence between the E-learning methodon the skills of students majoring in light vehicle engineering (TKR) SMK Negeri 3 Tahuan, as well as to find out the learning process of E-learning with the Skills of Students of the Light Vehicle Engineering Department (TKR) SMKNegeri 3 Tahuan. Based on the results of this study, there is a significant positive influence between the E-Learning Method and the Skills of Students of SMK Negeri 3 Tahuna, this can provide implications that with the existence of agood and appropriate E-Learning Method, it will be able to improve Student Skills, especially in the automotive field.